Human Umbilical Cord Mesenchymal Stem Cell-Derived Small Extracellular Vesicles Alleviate Lung Injury in Rat Model of Bronchopulmonary Dysplasia by Affecting Cell Survival and Angiogenesis - You, Jingyi; Zhou, Ou; Liu, Jiang; Zou, Wenjing; Zhang, Linghuan; Tian, Daiyin; Dai, Jihong; Luo, Zhengxiu; Liu, Enmei; Fu, Zhou; Zou, Lin (Stem cells and development, 2020)
Bronchopulmonary dysplasia (BPD) is a serious chronic lung disease in premature newborns, with high morbidity and mortality rates. Mesenchymal stem cell (MSC) transplantation has developed into a promising approach to alleviate BPD. Small extracellular vesicles, which are an important therapeutic component of MSCs, have been reported to be effective in a mouse model of BPD. However, the affected cell types and detailed underlying mechanisms are unclear. In this study, we found that human umbilical cord mesenchymal stem cell-derived small extracellular vesicles (hucMSC-sEVs) were successfully absorbed by lung tissue after intratracheal administration, and remained in the lungs for at least 72 h. The results showed that hucMSC-sEVs restored alveolar structure and lung function, and ameliorated pulmonary hypertension in a rat model of BPD. The number of Ki-67-positive lung cells were improved, while the number of TUNEL-positive lung cells were reduced in our hucMSC-sEV-treated BPD model. Additionally, SP-C staining (a marker of type II alveolar epithelial cells, TIIAECs) and CD31 staining (a marker of pulmonary vascular endothelial cells, PVECs) were both increased in a hyperoxia-induced BPD model treated with hucMSC-sEVs. In vitro, under hyperoxic conditions, the tube-like structure formation was improved in human umbilical vein endothelial cells, and the proliferation was increased and the apoptosis was attenuated in MLE-12 cells treated with hucMSC-sEVs. Furthermore, we observed downregulated expression of PTEN and cleaved-caspase3, and upregulated expression of p-Akt and vascular endothelial growth factor-A in our hucMSC-sEV-treated BPD model. In conclusion, hucMSC-sEVs improved alveolarization and angiogenesis in a rat BPD model by protecting TIIAECs and PVECs, which were associated with the PTEN/Akt signaling pathway.